Optimal energy and reserves scheduling through controllable charging and discharging a fleet of electric vehicles : doctoral thesis - Pavić, Ivan; Kuzle, Igor (Zagreb : I. Pavić; Faculty of electrical engineering and computing, 2021)
The increasing share of electric vehicles creates new challenges for both the power and the transport systems. The power system is affected at multiple levels, from distribution and transmission grid operation, through new balancing efforts, up to the long-term power system adequacy issues. To decrease the negative effect of electric vehicles on power system, uncontrollable charging can be replaced with smart charging concept (unidirectional or bidirectional controllable). Smart charging resembles charging (or discharging) in the periods when such action suits the power system. It could be in the form of energy arbitrage or provision of flexibility services. In this dissertation the focus is on the provision of balancing capacity and energy as flexibility services. Through dissertation tri main areas are processed which answer the following questions: can the smart charging positively affect the power system? How to increase the flexibility provision from electric vehicles towards the power system? How to approach the flexibility markets with adequate capacity, not jeopardizing technical feasibility and users' comfort?
Povećani udio električnih vozila stvara nove izazove i za elektroenergetski i za cestovni transportni sustav. E-mobilnost utječe na elektroenergetski sustav na nekoliko razina, od pogona distribucijske i prijenosne mreže, kroz nove zahtjeve za uravnoteženjem do problema dugoročne dostatnosti cijelog sustava. Kako bi se smanjio negativan utjecaj na elektroenergetski sustav električna vozila je moguće osim neupravljivim načinom, puniti i tzv. pametnim punjenjem (jednosmjerno ili dvosmjerno upravljivo). Pametno punjenje označava punjenje (ili pražnjenje) vozila u onim trenutcima kada to odgovara EES-u bilo da se radi o arbitraži električne energije ili o pružanju usluga fleksibilnosti. U ovom radu fokus je bio na pružanju kapaciteta i energije uravnoteženja kao usluga fleksibilnosti. Kroz disertaciju obrađena su tri osnovna područja koja daju odgovore na sljedeća pitanja: može li i kako pametno punjenja pozitivno utjecati na elektroenergetski sustav? Kako povećati mogućnost pružanja fleksibilnosti iz električnih vozila? Kako se flota električnih vozila može natjecati na tržištu električne energije i usluga uravnoteženja bez da se ugrožava izvodljivost izvođenja usluga ili komfor korisnika?